A "separation of worlds": The support and social networks of family carers of people with dementia at the end of life, and the possible role of the internet. (8th January 2019) - Davies, Nathan; Walker, Nina; Hopwood, Jenny; Iliffe, Steve; Rait, Greta; Walters, Kate
Abstract: Caring for someone with dementia is one of the most challenging caring roles; however, the demands of the role towards the end of life often mean carers are unable to maintain face‐to‐face support. The aim of this study was to: (a) Explore the experiences of older (over 65 years) family carers of people with dementia of support towards the end of life; (b) Explore with family carers the role of the internet as a support for them at the end of life. Semi‐structured interviews were conducted, with purposive sampling from general practice and research networks to recruit 20 current and former family carers aged 65 and over in England (2016–2017). Interviews were audio‐recorded, transcribed, and analysed using thematic analysis. An overarching theme of the "separation of worlds" (the internal caring world and the outside world of society) was identified, with four sub themes: (a) the support role of relationships and social networks; (b) loss as a consequence of caring; (c) reconstruction of life as a carer; and finally; (d) life within and beyond the computer screen. This study demonstrates the complexity of social support at the end of life for family carers depicted in a model of two worlds. The internet can be seen as a viable approach to help carers maintain existing networks, reconstruct networks they have lost or developing new networks to meet their new needs and circumstances as a carer. Future support interventions should focus on a mixed model of technology and human interaction.